MMORPG 이용자 충성도에 대한 영향요인간 구조적 관계 - 김정호(Jung-Ho Kim); 김유정(Yoo-Jung Kim); 강소라(Sora Kang) (한국콘텐츠학회 논문지, 10(12), 2010)
MMORPG makes up 25.9% of domestic market share in game industry, and it has become increasingly fierce in competition. Game developer and publisher make every effort to build customer e-loyalty to sustain their competitiveness. Thus, this paper examines the determinants of e-loyalty that reflect the features of MMORPG such as intensive and real-time interactivity. For this purpose, we selected interactivity, sense of community, reward and fun as the key antecedents of e-loyalty based on the extensive review of previous researches related to online game and Internet service usage. A total of 202 responses were used for analysis and the research results are as follow. The findings show that interactivity, sense of community and reward influence significantly on fun, then fun is positively related to e-loyalty. Also, interactivity and reward are proven to have a positive influence on sense of community, and sense of community mediates the effect of interactivity and reward on fun. MMORPG은 국내 게임시장의 25.9%를 차지하는 게임 장르로 최근에 다양한 게임이 출시되어 업체 간 경쟁이 치열해 지고 있는 산업이다. 이에 따라 게임업체에서는 충성도 높은 게임이용자 확보를 위해 다각도로 노력을 하고 있다. 따라서 본 연구의 목적은 MMORPG 게임 장르의 특성과 부합되는 MMORPG에 대한 이용자 충성도의 결정요인을 도출하고, 이러한 결정요인 간 구조적 관계가 이용자 충성도에 미치는 영향을 규명하는 것이다. 본 연구의 목적을 달성하기 위해 온라인 게임 및 인터넷 서비스 이용에 관한 선행연구를 검토하여 상호작용성, 공동체의식, 보상, 재미를 이용자 충성도의 결정요인으로 도출하였으며, 이들 연구변수 간 구조적 관계를 실증연구를 통해 검증하였다. 연구결과, 상호작용성, 공동체의식 및 보상이 재미에 유의미한 수준에서 긍정적인 영향을 미쳤으며, 재미는 이용자 충성도와 매우 강한 관계가 있는 것으로 나타났다. 또한 상호작용성과 보상은 공동체의식에 영향을 주었으며, 공동체의식을 매개로 재미에도 영향을 미치는 것으로 나타났다.